2017
DOI: 10.1111/bjd.15155
|View full text |Cite
|
Sign up to set email alerts
|

DOMINO, doxycycline 40 mg vs. minocycline 100 mg in the treatment of rosacea: a randomized, single-blinded, noninferiority trial, comparing efficacy and safety

Abstract: Minocycline 100 mg is noninferior to doxycycline 40 mg in efficacy over a 16- week treatment period. At follow-up, RosaQoL and PaGA were statistically significantly more improved in the minocycline group than in the doxycycline group, and minocycline 100 mg gives longer remission. In this study there was no significant difference in safety between these treatments; however, based on previous literature minocycline has a lower risk-to-benefit ratio than doxycycline. Minocycline 100 mg may be a good alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 45 publications
0
47
0
7
Order By: Relevance
“…A noninferiority study of minocycline 100 mg with doxycycline 40 mg MR was assessed as being at unclear risk of bias . Patients’ assessments showed that 22 of 40 participants with minocycline achieved excellent or good improvement vs. 20 of 40 in the doxycycline 40 mg MR group (RR 1·10, 95% CI 0·72–1·67; low‐certainty evidence).…”
Section: Resultsmentioning
confidence: 99%
“…A noninferiority study of minocycline 100 mg with doxycycline 40 mg MR was assessed as being at unclear risk of bias . Patients’ assessments showed that 22 of 40 participants with minocycline achieved excellent or good improvement vs. 20 of 40 in the doxycycline 40 mg MR group (RR 1·10, 95% CI 0·72–1·67; low‐certainty evidence).…”
Section: Resultsmentioning
confidence: 99%
“…In this issue of the BJD, van der Linden et al 4 report the findings of a randomized, non-inferiority trial comparing doxycycline 40 mg with minocycline 100 mg daily for papulopustular rosacea. Primary outcomes include overall lesion counts and patient's scores on a Rosacea-specific version of the Health-related Quality of Life questionnaire (RosaQoL).…”
mentioning
confidence: 99%
“…In ophthalmology, doxycycline is usually administered in patients affected by ocular rosacea and posterior blepharitis (18) . The doxycycline recommended dose is 40 mg modi ed release once daily, which could be replaced by minocycline 100 mg, based on patient tolerance or particular requirements (19) .…”
Section: Insights Into the Doxycycline Activitymentioning
confidence: 99%
“…The rationale in its administration is proteolysis inhibition promoted by matrix metalloproteinases (MMPs) (18,20) . MMPs are involved in the regulation of chemical and biological process likes vascular remodeling and angiogenesis (21) , so doxycycline also has anti-angiogenic properties (22) .…”
Section: Insights Into the Doxycycline Activitymentioning
confidence: 99%